The Fauna Lexicon in Aceh Proverb: Ecolinguistic Study - Gumarpi Rahis Pasaribu; Dwi Widayati; Aron Meko Mbete; Dardanila Dardanila (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
The reciprocal relationship between humans and humans, humans and the nature around them, produces a variety of languages. Ecolinguistics is needed in studying aceh language phenomena. This study aims to describe the meaning, function, and form of the fauna lexicon in the culture of the people of Aceh. This research is descriptive-qualitative in nature. This research data collection technique consists of interview techniques and observation techniques. Interview techniques were used to obtain data on the meaning and function of fauna in the culture of the people of Aceh. While observation techniques are used to obtain data on fauna forms in the culture of the people of Aceh. Current facts show that the lexicon of fauna is still used by parents when advising the younger generation, and they cannot understand the meaning of the advice. This is caused by environmental changes and the times that affect the younger generation’s mindset. The researcher collected a list of fauna lexicons in the Acehnese language and classified them into verb and noun classes.